The Comparison of Gut Bacteria Communities and the Functions Among the Sympatric Grasshopper Species From the Loess Plateau - Zhao, Lu; Wang, Wen-Qiang; Xu, Sheng-Quan; Guan, De-Long (Frontiers in Microbiology, 2022)
Gut bacteria exert effects on the health and fitness of their insect hosts. Grasshoppers are an important part of the grassland ecosystem and provide important ecosystem services. As the most valuable feature in grassland ecosystem, the compositions and potential influences of gut bacterial in herbivorous grasshoppers in the same ecological environment are essential but undetermined. To facilitate such studies, we collected nine species of grasshoppers (n = 110) from a rebuild grassland on the Loess Plateau in northern Shaanxi, China, which is a representative area of ecosystem restoration model. We characterized the composition and function of the gut bacteria. We found that 326 OTUs were exhibited in all grasshoppers in which Enterobacter, Pantoea, Bacillus, and Spiroplsma are dominant. Among them, 18 OTUs were shared across all nine species of grasshoppers. The predicted function showed that the majority function of those OTUs were involved in survival dependent processes including membrane transport, carbohydrate metabolism, amino acid metabolism, and DNA replication and repair. The composition of gut bacteria is specific to each grasshopper species, and the bacteria community is most various in Trilophidia annulata. These results highlight the gut bacterial community diversity in different grasshopper species. Our findings are necessary for better understanding the relationships between this important herbivorous insect and their microbiomes and have the potential contribution of evaluating the revegetation and ecosystem management in this area.